Effect of preoxygenation using non-invasive ventilation before intubation on subsequent organ failures in hypoxaemic patients: a randomised clinical trial. (February 2018) - Baillard, C.; Prat, G.; Jung, B.; Futier, E.; Lefrant, J.Y.; Vincent, F.; Hamdi, A.; Vicaut, E.; Jaber, S.
Abstract: Background: Previous data showed that non-invasive ventilation (NIV) applied for 3 min before tracheal intubation ensured better oxygenation compared with using a non-rebreather bag-valve-mask. We aimed to determine whether preoxygenation using NIV is effective in reducing the incidence of organ dysfunction in hypoxaemic, critically ill patients in intensive care. Methods: A multicentre, randomised, open-label trial evaluating 100% FiO2 administered with NIV (99 patients) vs with face mask (102 patients) for 3 min before tracheal intubation. The primary endpoint was the maximal value of Sequential Organ Failure Assessment score within 7 days after intubation. Results: The median (inter-quartile range) values of the maximal value of the Sequential Organ Failure Assessment score within 7 days post-intubation were not significantly different between the two randomised groups: nine (6–12) in the NIV group vs 10 (6–12) in the face mask group ( P =0.65). In patients treated by NIV prior to the randomisation, there was a significant increase in the occurrence in adverse events in patients randomised to face mask [odds ratio=5.23 (1.61;16.99), P =0.0059]. Conclusions: This study failed to demonstrate any benefits of using NIV as a preoxygenation method to reduce organ dysfunction compared with usual preoxygenation in hypoxaemic, critically ill patients requiring tracheal intubation for invasive ventilation. NIV should not be discontinued for preoxygenation in the cases of patients treated by NIV before the decision to intubate. Clinical trial registration: NCT00472160.